Efficacy of Postoperative Polymyxin B Hemoperfusion in Secondary Peritonitis Patients with Septic Shock: A Propensity-Matched Analysis. Issue 12 (December 2016) - Yuan, Kuo-Ching; Wang, Shang-Yu; Yu, Ming-Chin; Hsu, Yu-Pao; Pan, Heng-Chih; Chen, Yung-Chang
Introduction: Severe sepsis and septic shock is still a challenge. Polymyxin B hemoperfusion (PMX) is a device designed to remove circulating endotoxin by adsorption, which is reported to improve treatment outcomes. This study aimed to further verify the efficacy of PMX on postoperative, peritonitis, septic shock patients. Methods: This study prospectively analyzed 20 of 155 patients who presented with postoperative septic shock and were treated with PMX in a single institute during the period March 2013 to September 2014 (Clinical Trial Protocol number: ChiCTR-ONC-16008160). A control group (53 patients) was recruited from our own 2012 database using the propensity-matching score method. The data collection includes demographic data, postoperative organ dysfunction status, disease severity and treatment result. Results: The 2 groups (treatment vs. control) were similar in demographic data, organ dysfunction status and disease severity. PMX use provides benefits for recovery of hemodynamic status and many other aspects, including better survival, but is not statistically significant. For survival factor analysis, PMX use is also not significant for patient survival in our study. Conclusions: PMX provided some benefits to patients in the treatment for peritonitis septic shock. An improvement in hemodynamic status was mostly observed. Our study also supports the finding that PMX used as an auxiliary treatment provides improved survival but is not statistically significant, possibly due to the small sample size with multiple comorbidities.